The Contribution of CLIP2 Haploinsufficiency to the Clinical Manifestations of the Williams-Beuren Syndrome - Vandeweyer, Geert (Elsevier, 2012)
Williams-Beuren syndrome is a rare contiguous gene syndrome, characterized by intellectual disability, facial dysmorphisms, connective-tissue abnormalities, cardiac defects, structural brain abnormalities, and transient infantile hypercalcemia. Genes lying telomeric to RFC2, including CLIP2, GTF2I and GTF2IRD1, are currently thought to be the most likely major contributors to the typical Williams syndrome cognitive profile, characterized by a better-than-expected auditory rote-memory ability, a relative sparing of language capabilities, and a severe visual-spatial constructive impairment. Atypical deletions in the region have helped to establish genotype-phenotype correlations. So far, however, hardly any deletions affecting only a single gene in the disease region have been described. We present here two healthy siblings with a pure, hemizygous deletion of CLIP2. A putative role in the cognitive and behavioral abnormalities seen in Williams-Beuren patients has been suggested for this gene on the basis of observations in a knock-out mouse model. The presented siblings did not show any of the clinical features associated with the syndrome. Cognitive testing showed an average IQ for both and no indication of the Williams syndrome cognitive profile. This shows that CLIP2 haploinsufficiency by itself does not lead to the physical or cognitive characteristics of the Williams-Beuren syndrome, nor does it lead to the Williams syndrome cognitive profile. Although contribution of CLIP2 to the phenotype cannot be excluded when it is deleted in combination with other genes, our results support the hypothesis that GTF2IRD1 and GTF2I are the main genes causing the cognitive defects associated with Williams-Beuren syndrome.